2011
DOI: 10.1089/jmf.2010.0040
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Probiotics and α-Tocopherol on Ethanol-Induced Gastric Mucosal Injury in Rats

Abstract: The protective effect of a probiotic mixture of 13 different bacteria and α-tocopherol on 98% ethanol-induced gastric mucosal injury was evaluated. Levels of gastric mucosal pro- and anti-inflammatory cytokines, malondialdehyde, and secretory immunglobulin A were measured. Rats were allocated into four groups: control, ethanol, probiotic, and α-tocopherol. The control and ethanol groups received skim milk for 14 days. Probiotic and α-tocopherol groups were administered probiotic mixture suspended in skim milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
1
16
0
1
Order By: Relevance
“…As previously mentioned, many other studies had also demonstrated the involvement of inflammation in the pathogenesis of gastric lesions. Many pro-inflammatory biomarkers have been identified in various models of gastric lesions (Oh et al, 2005;Senol et al, 2011). On one hand, interferon-g (IFN-g) was significantly elevated in rats subjected to water-immersion restraint with H. pylori infection but no elevation was seen in the group with H. pylori infection only.…”
Section: Inflammation In Gastric Mucosamentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, many other studies had also demonstrated the involvement of inflammation in the pathogenesis of gastric lesions. Many pro-inflammatory biomarkers have been identified in various models of gastric lesions (Oh et al, 2005;Senol et al, 2011). On one hand, interferon-g (IFN-g) was significantly elevated in rats subjected to water-immersion restraint with H. pylori infection but no elevation was seen in the group with H. pylori infection only.…”
Section: Inflammation In Gastric Mucosamentioning
confidence: 99%
“…It seems that IFN-g has a more important role in stress than TNF-a. In the ethanol-induced model, other than the two cytokines (IFN-g and TNF-a), interleukin-2 (IL2) and interleukin-4 (IL4) levels were also augmented (Senol et al, 2011). These cytokines have important roles in gastric inflammation (Oh et al, 2005).…”
Section: Inflammation In Gastric Mucosamentioning
confidence: 99%
“…Senol et al . () demonstrated that ethanol exposure tended to increase mucosal TNF‐α, IFN‐γ, IL‐2 and IL‐4. Park et al .…”
Section: Discussionmentioning
confidence: 98%
“…Production of proinflammatory cytokines by NF-κB activation can act as a positive autocrine amplification feedback signal to NF-κB activation as well as paracrine amplification, thereby causing amplification loops of inflammation (Coward et al 2002). Senol et al (2011) demonstrated that ethanol exposure tended to increase mucosal TNF-α, IFN-γ, IL-2 and IL-4. Park et al (2008) reported that ethanol ingestion increased the stimulation of IL-1β, IFN-γ and IL-10 in gastric mucosa compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the experimental rats infected with S. dysenteriae but not treated suffered from shigellosis, while the test groups infected and treated with the L. casei showed no sign of the disease as well as no clinical effect on the liver. Senol et al (2011a) investigated the protective effect of a probiotic mixture of 13 different bacteria and a-tocopherol on 98% ethanol-induced gastric mucosal injury. Levels of gastric mucosal pro-and anti-inflammatory cytokines, malondialdehyde, and secretory immunglobulin A were measured.…”
Section: Effects Of Probiotics On Human Healthmentioning
confidence: 99%